A Facile Method for the Synthesis of Betrixaban. (September 2015) - Li, Jianye; Chen, Ligong; Yan, Xilong; Li, Yang; Wei, Daiyan; Wang, Donghua
A facile method for the synthesis of N-(5-chloropyridin-2-yl)-2-(4-(N, N-dimethylcarbamimidoyl)benzamido)-5-methoxybenzamide (Betrixaban) from 5-methoxy-2-nitrobenzoic acid is achieved by reduction, acylation, chlorination, acylation and the formation of the amidine. A dechlorinated impurity is avoided in this method. Using tetrahydrofuran as the solvent in the four steps makes its recovery easier. The total yield of the target compound is about 40% and this method is suitable for large-scale production.